THE ROLES OF WRITING ATTITUDES AND WRITING APPREHENSION IN EFL LEARNERS’ WRITING PERFORMANCE - Ni'mah, Ulin; Kadarisman, A. Effendi; Suryati, Nunung (LET: Linguistics, Literature and English Teaching Journal, 2016)
The present study used a mixed method research design since it aimed at examining the degree of relationship between the students? writing attitude, apprehension, and writing performance and investigating the causes of both factors. The finding of the study revealed that there was a significantly positive correlation between attitude towards writing and learners? writing performance (r=.240 and sig=.049<.05) and the difference of performance was significant (Sig.= .018 < .05). The writing apprehension and writing performance were significantly negatively correlated (r=-.246, sig=.043) and the difference of performance was significant (Sig.= .000< 0.05). The interview result showed several factors causing the students? writing attitude and apprehension. The positive attitudes were caused by the importance of English as an international language, the relationship of English and science, the interest in writing and English, and the lecturer?s evaluation. Students having negative attitude confessed that they were not good at English, writing in English was a difficult activity, and they did not write much. Low writing apprehension was caused by the interest in writing, being good at grammar and vocabulary, and positive thinking in completing the task. At last, students with high apprehension thought that they were afraid of making mistakes; since they were not good at English, they tended to translate bahasa Indonesia into English, and they were not able to develop topics given by the lecturer.